A wonder-book and Tanglewood tales - Hawthorne, Nathaniel (Riverside bookshelf, 1923)
Tales told at the fireside and in the woods, adapting such classical myths as Pandora's Box, Baucis and Philemon, and Perseus and Medusa to the storyteller's gothic or romantic environment.